Karakteristik Virgin Coconut Oil (VCO) dan Protein Krim Santan yang Diektraksi dengan Metode Pancingan - Parwiyanti, Parwiyanti; Lidiasari, Eka; Yudono, Bambang; Aprilia, Rantika; Debi Yora, Riska (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2022)
Parwiyanti P, Lidiasari E, Yudono B, Aprilia R, Yora RD. 2022. Characteristics virgin coconut oil (VCO) and protein of coconut milk cream extracted by fishing method. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 337-345. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The coconut product that has high added value as a raw material for cosmetics and medicine was Virgin Coconut Oil (VCO). The objective of this research was to determine effect of the concentration induced VCO and the speed of stirring on the VCO and protein characteristics of coconut milk cream. The experiment used a Factorial Completely Randomized Design with two factors. The first factor was VCO concentration consisting of 3 levels (5%, 7%, and 10%) and the second factor was stirring speed consisting of 3 levels (500, 700, and 900 rpm). The parameters were yield, moisture, free fatty acids, degree of clarity and peroxide number for VCO and yield, moisture, ash and protein content for protein. The results for VCO showed that the concentration of induced VCO had a significant effect on the yield, stirring speed had a significant effect on the value of free fatty acids, the interaction of the two treatment factors had a significant effect on the value of the degree of clarity. The best treatment for VCO was induced VCO concentration of 5% and stirring speed of 500 rpm. For protein: the interaction of the induced VCO and stirring speed had significant effect on water and protein content. The best treatment for protein was obtained in the 10% induced VCO concentration and stirring speed of 900 rpm.